Telemedicine utilisation in a paediatric sports medicine practice: decreased cost and wait times with increased satisfaction. Issue 2 (1st February 2018) - Atanda, Alfred; Pelton, Miguel; Fabricant, Peter D; Tucker, Ashley; Shah, Suken A; Slamon, Nicholas
Abstract : Objectives: Telemedicine is the use of telecommunication to provide healthcare remotely. We sought to quantify time/cost savings and satisfaction between a cohort of telemedicine and inperson visits in a tertiary paediatric orthopaedic clinic. Methods: Time for clinical visits and wait times were compared between telemedicine and inperson visits. Costs to patients and department were also calculated for both visit types. Parents completed a five-item satisfaction survey regarding their telemedicine experience. Results: Visit times (15 vs 68 min, P<0.001) and wait times (2 vs 33 min, P<0.001) were shorter for telemedicine visits. Families saved 85 miles of driving and 50 in costs per telemedicine visit. Labour cost saved for a telemedicine visit was 24/patient. More than 90% of patients were satisfied with the telemedicine service. Conclusion: Telemedicine can be used in a sports medicine setting to provide care that reduces costs while maintaining high levels of patient satisfaction. Level of evidence: Level III.